Anti-Müllerian hormone, sex steroids, and metabolic profile in cord blood of pregnancies with type 2 diabetes and gestational diabetes - Villarroel, Claudio; López, Patricia; Henriquez, Soledad; Kohen, Paulina; Codner, Ethel (Frontiers in Endocrinology, 2025)
ContextThe prevalence of type 2 diabetes (T2D) and gestational diabetes (GD)among women of reproductive age has increased in recent decades, making it the most common pregnancy complication. Many studies have examined pregnancy complications in women with diabetes; however, the impact of diabetes on the intrauterine environment, specifically ovarian markers and metabolic profiles in very preterm infants at birth, has not been studied. This study aimed to investigate AMH, sex steroid levels, and the metabolic profile in venous cord blood (VCB) in gestations affected by type 2 diabetes (T2D) and gestational diabetes (GD).Material and methodsHormonal profile was evaluated in VCB of pregnancies with T2D (n=24), GD (n=26), and pregnancies without diabetes (C, n=25). Only pregnancies carrying a female offspring were included. AMH, sex steroids, and metabolic function biomarkers, including glucose, insulin, IGF-1, and adiponectin (APN) were measured. Clinical and anthropometric data were assessed in the mothers and offspring.ResultsAMH VCB levels were significantly higher in T2D than in GD and C pregnancies (P<0.01 and P<0.005, respectively). Dehydroepiandrosterone sulfate (DHEAS) and sex hormone-binding globulin (SHBG) VCB levels were lower in T2D pregnancies than in GD and C (P < 0.01, P < 0.0001, respectively). APN levels were lower in T2D pregnancies than in C (P < 0.05). Additionally, higher insulin and IGF-1 VCB levels and HOMA-IR index were observed in T2D than in C and GD (P < 0.001, P<0.05, and P<0.05, respectively). No significant correlations were observed between maternal and AMH, insulin, IGF-1, and androgen VCB levels.DiscussionT2D disrupts the intrauterine environment, leading to increased insulin, IGF-1, HOMA-IR, and AMH concentrations and decreased adiponectin levels in VCB. These findings describe the impact that maternal T2D may have on the health and development of their offspring.